Complications and mistakes after anterior cervical interbody fusion with autologous bone grafts - Barysh, Oleksandr; Fedoryna, Eduard (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Full coalescence after the anterior interbody fusion using bone cortical-cancellous iliac crest autografts and rigid plates in the surgical treatment of fresh injuries of the cervical spine may be reached in 95–100 % of cases. Despite on this the number of unsatisfactory results of operations related to bone graft amounts 50.7 %, and complications due to the use of hardware can range from 5 % to 35 %. Objective: To analyze the complications and mistakes after the anterior interbody bone fusion using cortical-cancellous iliac crest autografts and rigid plates in cases of surgical treatment of the subaxialcervical functional spinal units’ injuries. Material and Methods: There were analyzed outcomes in 123 patients with fresh cervical spine injuries, 91 (73.9 %) men and 32 (26.08 %) of women aged from 16 to 67 years among them. For all patients we performed decompressive and stabilizing surgeries by means of bone cortical-cancellous autografts from the ipsilateral iliac crest and rigid plates developed at the Institute according to known and designed at the Institute techniques. Time from injury to surgery ranged from 3 to 42 hours (mean, 9.54 hours), and duration of surgery ranged from 90 to 210 minutes (average, 1 hour 50 minutes). All patients were examined clinically and radiologically by known methods. Results: An interbody fusion was achieved in 95.8 % of cases, and the overall complication rate was 30.9 %. All complications and mistakes were systematized and analyzed. The greatest number of complications was associated with metal constructs (11.38 %), with bone graft implemented in interbody space (4.87 %) and occurred on the site of the donor wound (5.69 %). The least amount of complications was observed at the postoperative cervical wound region (3.24 %). Conclusions: Enhancement of a technique for the anterior interbody fusion by means of bone autografts and cervical rigid plates and careful compliance with the principles of stabilization of the cervical functional spinal units as well as rules for such surgeries will prevent technical mistakes, reduce the number of complications and improve outcome.